Heavy Metal in Hallowed Contexts. Continuity and change in aes deposits in Central Italy and Sicily - Murgan, Andreas (Embodying Value? The Transformation of Objects in and from the Ancient World, 2014)
Amongst the numerous finds from the middle and second half of the first millennium BC discovered in sacred contexts in Central Italy and Sicily, the uncoined metal (mainly known as aes rude and aes signatum) found in temples and graves is relatively understudied. Through their archaeological contexts, these pieces can reveal practical and theoretical aspects surrounding cult practices. This article uses comparatively well published examples of such metal finds, in conjunction with other historical sources, to consider the religious deposition of these objects, which has a long tradition in this region that continued throughout the period of Roman expansion and lasted until at least the late Republic. This raises questions about the purposes of this material across time, space (Italy or Sicily), place (temples or graves), and continuity and change in ritual behaviour. Learning more about the aim, function and the embodied value(s) of aes in sacred contexts can lead to a better understanding of its use as a votive, sacrifice, or gift to the deceased.